LANGUAGE LEARNING STRATEGIES IN E-LEARNING USED BY INTERNATIONAL CLASS STUDENTS MAJORING IN ENGLISH LITERATURE UNIVERSITAS BRAWIJAYA - Syahputra, Reza Kurnia; Hamamah, Hamamah (Universitas Negeri Malang, 2022)
This article reports the findings of a study conducted in English Literature at the Faculty of Cultural Studies in Universitas Brawijaya in 2020. The research focused on the most frequent language learning strategies used by 20 international program students’ batch of 2017 that have been conducted the Overseas Academic Program (OAP). For the data collection, data were gained from Strategy Inventory for Language Learning (SILL) questionnaire version 7.0 in the form of online. The results of the study showed that the most frequent strategy used by batch of 2017 international class students is compensation strategy with an average 3.82. When the class of 2017 as EFL learner conducted the Overseas Academic Program (OAP), they were required to communicate with English speakers using English and when they forgot a vocabulary, they changed it using gestures to keep the conversation going and then tried to guess what the interlocutor would say after.